Ontological (In)Security - Art Students' Experience of Agency in the Educational Reality During the Pandemic - Agnieszka Weiner (Ignatianum University Press, 2023)
Objectives of the study: The purpose of the study is to reconstruct the experiences of art students during the Covid-19 pandemic. The research question is as follows: What image of the everyday life of remote education emerges from the reconstruction of the experiences of students who were previously assigned to extreme groups in terms of their perceived proficiency? Research methods: Due to the different objectives' for specific questions - involving nomothetic explanation in some areas (basic descriptive statistics, comparison of selected subfields, logistic regression) and idiographic explanation in others (qualitative content analysis) - the research used a quantitative and qualitative strategy. Brief description of the context of the issue: Art schools provide unique educational opportunities as teachers-artists have a personal influence on students through face-to-face interaction. The pandemic has presented these schools with an unprecedented challenge, on a scale that had not been seen before. In the research presented here, voice was given to the students, who were considered experts in their own cause. Their experiences, as a multidimensional construct, were located theoretically in the context of the threefold framework of temporal order, space and relationship, and Bruner's concept of the role of support in child development. Research findings: The results show a link between perceived levels of ontological security and the way students functioned at school during the pandemic. Psychological well-being was affected more strongly in those with a low sense of agency, who often balanced on the verge of ontological security and experienced reality in a traumatic way, while students with a high sense of agency tended to focus on the benefits rather than losses. Conclusions and/or recommendations: Locating students on the continuum of a sense of agency brought a fresh perspective on the different ways in which young artists with and without a disturbed sense of ontological security experienced school during the pandemic. Important recommendations include continuing multidirectional support measures of a pedagogical and psychological nature undertaken by many institutions, which should be aimed at art students, their parents and teachers.